2014
DOI: 10.1155/2014/472625
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 Receptors Are Differentially Expressed in Normal and Psoriatic T Cells

Abstract: This study was carried out to examine the possible role of interleukin-1 (IL-1) in the functional insufficiency of regulatory T cells in psoriasis, by comparing the expression of IL-1 receptors on healthy control and psoriatic T cells. Patients with moderate-to-severe chronic plaque psoriasis and healthy volunteers, matched in age and sex, were selected for all experiments. CD4+CD25− effector and CD4+CD25+CD127low regulatory T cells were separated and used for the experiments. Expression of the mRNA of IL-1 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…However, we observed that YCA supplementation tended to increase gene expression of the thiol protease CASP1, which activates IL-1b, and increased gene expression of IL1R1, one of the two units of the IL-1 receptor that binds to activated IL-1b. 22,23 The other genes affected by YCA supplementation included the pro-apoptotic transmembrane protein FASLG and the protease CASP8, which are molecular targets of TNF-a signaling, and the transmembrane protein IFN-aR1, which is the receptor for IFN-a signaling. In summary, dietary YCA may potentiate TLR signaling.…”
Section: Dietary Yca Increased Expression Of Genes Involved In Tlr Simentioning
confidence: 99%
“…However, we observed that YCA supplementation tended to increase gene expression of the thiol protease CASP1, which activates IL-1b, and increased gene expression of IL1R1, one of the two units of the IL-1 receptor that binds to activated IL-1b. 22,23 The other genes affected by YCA supplementation included the pro-apoptotic transmembrane protein FASLG and the protease CASP8, which are molecular targets of TNF-a signaling, and the transmembrane protein IFN-aR1, which is the receptor for IFN-a signaling. In summary, dietary YCA may potentiate TLR signaling.…”
Section: Dietary Yca Increased Expression Of Genes Involved In Tlr Simentioning
confidence: 99%
“…Our data are fully consistent with the literature on the level of IL1R1 and IL1R2 mRNAs in T cells. 23 Additionally, this comparison of mononuclear cell subpopulations has shown that a higher percentage of the CD14 1 monocytes population were also IL1R1 1 . The CD19 1 B lymphocytes showed the lowest percentage of IL1R1 1 cells.…”
Section: Discussionmentioning
confidence: 83%
“…21,22 Differing expression levels of IL-1 receptors type 1 and 2 have previously been shown in T-lymphocyte populations. 23 Moreover, prior studies have examined the association of polymorphisms in the IL-1 receptor genes with different diseases. However, data on association of these polymorphisms with receptor protein expression levels have not yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…Auch Mikrodialyse-Experimente konnten eine Erhöhung von IL-1β in der Gewebsflüssigkeit der erkrankten Haut von Psoriasispatienten nachweisen, welche sich unter Therapie normalisierte [56]. T-Helferzellen von PsO-Patienten zeigen zudem nach Aktivierung eine stärkere Hochregulation des IL-1RI als gesunde T-Helferzellen und somit eine erhöhte Suszeptibilität für die IL-1β-nachgeschaltete Signalkaskade [57]. Ferner konnte eine Assoziation zwischen Polymorphismen im IL-1RA-Gen auf der einen Seite und "early-onset"-und "late-onset"-PSO auf der anderen Seite festgestellt werden [58].…”
Section: Psoriasis Vom Plaque-typunclassified